Maritime Decentralization and Blue Governance within the Framework of Regional Autonomy: A Systematic Literature Review - Ayunytyah Eka Wardani; Tri Cahyo Nugroho; Andi Rahmat Nizar Hidayat (Universitas Muhammadiyah Makassar, 2026)
Maritime decentralization and blue governance have emerged as strategic issues in contemporary marine governance reforms, particularly within the framework of regional autonomy. This article examines the conceptual relationship and evolving literature on maritime decentralization and blue governance using a systematic literature review (SLR) approach. The review process followed PRISMA guidelines and included peer-reviewed publications published between 2019 and 2024. The findings indicate that maritime decentralization has evolved from administrative deconcentration toward substantive devolution and more collaborative polycentric governance models. The effectiveness of decentralization is strongly influenced by multi-level governance configurations, particularly vertical coordination and horizontal cross-actor participation. Meanwhile, blue governance has developed as a normative paradigm emphasizing ecological sustainability, equitable benefit distribution, transparency, and community participation in marine resource management. In the Indonesian context, the implementation of blue governance faces challenges related to regulatory harmonization and subnational institutional capacity following marine authority reforms. The study concludes that maritime decentralization can only achieve its intended outcomes when embedded within an adaptive multi-level governance framework aligned with the principles of blue governance. Keywords: maritime decentralization; blue governance; regional autonomy; multi-level governance; marine governance; systematic literature review